Mental health symptoms and coping strategies among Ukrainians during the Russia-Ukraine war in March 2022 - Xu, Wen; Pavlova, Iuliia; Chen, Xi; Petrytsa, Petro; Graf-Vlachy, Lorenz; Zhang, Stephen X. (International Journal of Social Psychiatry, 2023)
Context: The Russian attack on Ukraine has been ongoing since February 24, 2022. Nevertheless, no research has documented the mental health of Ukrainians during the biggest land war in Europe after the Second World War, or how Ukrainians cope with the impact of the war. Objectives: To provide the prevalence rates of symptoms of psychological distress, anxiety, depression, and insomnia; and to link them with Ukrainians’ productive coping strategies during the war. Design, setting, and participants: Online survey conducted in Ukraine during the initial period of the Russian invasion (March 19–31, 2022), using a quota sampling method, of 1,400 Ukrainians aged 18 years or older, with a total of 801 valid responses for a response rate of 57.2%. Main outcome measures: Psychological distress assessed by the Kessler Psychological Distress scale (K6); anxiety assessed by Generalized Anxiety Disorder-2 (GAD-2) scale; depression assessed by Patient Health Questionnaire-2 (PHQ-2); insomnia assessed by Insomnia Severity Index-4 (ISI-4); modes of coping assessed by Brief COPE. Results: Of 801 Ukrainian adults, 52.7% had symptoms of psychological distress (mean = 13.3 [SD = 4.9]); 54.1% of them reported symptoms of anxiety (mean = 2.9 [SD = 1.7]); 46.8% reported symptoms of depression (mean = 2.6 [SD = 1.6]). Symptom criteria for insomnia were met by 97 respondents (12.1%) (mean = 10.4 [SD = 4.2]). Demographic variables (including gender, living in an urban area, having children or elderly persons in the household, living in an area occupied by Russian forces) were associated with symptoms of distress, anxiety, depression, and insomnia. The productive coping strategies of using instrumental support, behavioral disengagement, self-distraction, and planning were significantly associated with mental health symptoms. Conclusions: Prevalence rates of symptoms of psychological distress, anxiety, depression, and insomnia were high. These findings underscore the need for healthcare and productive coping strategies for Ukrainians during the war.
CRIS-Team Scopus Importer:2026-04-08
Keywords: anxiety; coping strategies; depression; insomnia; psychological distress; Russia-Ukraine war